Microwave‐Positioning Assembly: Structure and Surface Optimizations for Catalysts. Issue 3 (10th March 2022) - Xiao, Shuning; Huo, Mengjia; Guan, Yuchuan; Cao, Haiyan; Huang, Qian; Chen, Linglong; Li, Shuangjun; Li, Guisheng; Zhang, Dieqing; Li, Hexing
Abstract : Microwave‐Positioning Assembly Based on the superhot characteristics of specific materials under microwave irradiation, various new composites with hierarchical structure and amazing properties can be synthesized through a facile microwave‐heating approach. In article number 2100169, Shuning Xiao, Dieqing Zhang, Hexing Li, and co‐workers propose the basic concepts of microwave‐positioning assembly and summarize the recent progress in catalyst synthesis and function development. This novel synthesis method provides an effective way for materials preparation and optimization, which may offer more opportunities for developing powerful catalysts used in energy and environmental areas.